Hubungan Pemberian Makanan Pendamping ASI Dengan Kejadian Stunting Pada Anak Umur 6-24 Bulan - Wa Ode Nombi; Asnia Zainuddin; Febriana Muchtar (KOLONI, 2023)
Stunting is characterized by impaired growth, indicated by height or length measurements below -2 standard deviations (SD) for a given age. Chronic malnutrition during pregnancy and up to the age of 2 is the primary cause of stunting. Adequate nutrient intake plays a crucial role in preventing stunting. When infants reach 6 months of age, complementary feeding is introduced to meet their nutritional requirements. This study aimed to investigate the relationship between complementary feeding practices and the prevalence of stunting among children aged 6-24 months in the working area of the Batuatas Community Health Center, South Buton Regency. The qualitative data in this case-control study were analyzed using the Chi-Square test and Odds Ratio (OR). The findings revealed a significant correlation between stunting prevalence and mothers' knowledge about complementary feeding (p-value = 0.019, OR = 0.40). Moreover, the timing of complementary feeding introduction also had a significant impact on stunting prevalence (p-value = 0.032, OR = 0.43). Keywords: Children Aged 6-24 Months, Complementary Feeding, Mothers’ Knowledge